Prophylactic administration of metformin alleviates withdrawal symptoms associated with heroin - Liu, Minghong; Jiang, Junyu; Wu, Xiaolong; Liu, Jiaxin; Liu, Yang; Ling, Shanshan; Chen, Huichun; Zhang, Gongliang; Li, Yuanhai; Pang, Gang; Tao, Xinrong (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate whether metformin can alleviate heroin withdrawal symptoms and explore its underlying mechanisms, focusing on its reducing microglia-related neuroinflammation in the CA3 region of hippocampus.MethodsWe set up a heroin withdrawal mouse model by the administration of naloxone in heroin-treated mice. To reduce experimental variables, only male mice were considered in this study. The behaviors of withdrawal model mice with saline, naloxone (5 mg/kg), or metformin (100 mg/kg) treatment (n = 12 for each group) were evaluated by Open Field Test (OFT) and Elevated Plus Maze Test. After the behavior tests, brain tissues were collected for histological staining experiments. Our study mainly focused on the hippocampal CA3 region. Protein expression levels of TLR4 (inflammation related) and BAX were analyzed using immunofluorescence staining.ResultsMetformin was proved to be capable of improving movement-related and posture-related behavioral changes caused by the naloxone-induced heroin withdrawal. Furthermore, the results of the Open-Field Test and Elevated Plus Maze test were used to demonstrate metformin’s role in softening anxiety levels, which was due to its reducing microglia-related neuroinflammation in the CA3 region of hippocampus. This neuronal protection was achieved by downregulating the expression of TLR4 (inflammation related) and BAX (apoptosis marker) protein.ConclusionOverall, our data suggests that prophylactic administration of metformin has a therapeutic effect on glial-induced neuroinflammation and neuronal apoptosis in heroin withdrawal mice. Histological experiments suggested that metformin reduced microglia-mediated neuroinflammation and downregulated TLR4 and BAX expressions in the hippocampus.